STRUCTURE OF THE PLANKTON COMMUNITY IN THE TECHNICAL IMPLEMENTING UNIT OF FRESHWATER AQUACULTURE PRODUCTION IN BANJARBARU, SOUTH KALIMANTAN - Normila Sari; Abdur Rahman; Deddy Dharmaji (Fish Scientiae, 2022)
Plankton is an important organism forming the food chain and material cycle in the waters. Plankton is divided into two groups, namely the group of phytoplankton (plant plankton) and zooplankton (animal plankton). These two organisms has an important role, namely as producers and consumers in one ecosystem (Aini et al., 2018). It has important role in a waters as a primary producer and bioindicator of the fertility level of a waters. The results of calculating the average value of plankton abundance in weeks 1, 2, 3, and 4 of phytoplankton are 35,523 cells/l and zooplankton are 16,327 ind/l, plankton diversity index values in weeks 1, 2, 3, and 4 of phytoplankton are 1.967 cells/l and zooplankton are 1.091 ind/l. The results of calculations using the STORET method in week 1 with a total score (-10), week 2 with a total score (-1), week 3 with a total score (0), and week 4 with a total score ( -12). The difference in these values is influenced by several factors and differences in the values of water quality measured during the study.